Mediators of Inflammation in Acute Kidney Injury. (27th December 2009) - Akcay, Ali; Nguyen, Quocan; Edelstein, Charles L.
Abstract : Acute kidney injury (AKI) remains to be an independent risk factor for mortality and morbidity. Inflammation is now believed to play a major role in the pathopathophysiology of AKI. It is hypothesized that in ischemia, sepsis and nephrotoxic models that the initial insult results in morphological and/or functional changes in vascular endothelial cells and/or in tubular epithelium. Then, leukocytes including neutrophils, macrophages, natural killer cells, and lymphocytes infiltrate into the injured kidneys. The injury induces the generation of inflammatory mediators like cytokines and chemokines by tubular and endothelial cells which contribute to the recruiting of leukocytes into the kidneys. Thus, inflammation has an important role in the initiation and extension phases of AKI. This review will focus on the mediators of inflammation contributing to the pathogenesis of AKI.